RESPON PERTUMBUHAN TOMAT (Lycopersicum esculantum) PADA BERBAGAI JENIS MULSA DAN FREKUENSI PENYIRAMAN DI KWT LA’O - Adi, Defiyanto Djami; Ngajang, Oskariano Oskarianus Yondri Saputra; Jaya, Ertilinda Sinarti; Maya, Maria Astina; Adur, Agustinus; Karno, Yonarius (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2024)
The vegetable plant that is in great demand and has economic value is the tomato plant (Solanum lycopersicum). The use of mulch will affect soil temperature and moisture so that it can overcome the lack of water. This study aims to determine the best type of mulch and watering frekuency to support the growth and production of tomato plants. This research has been carried out in the agricultural land of the La'o farmer women's group, Wali sub-district, Langke Rembong sub-district, Manggarai regency. The experiment used a two-factor Group Randomized Design (RAK), namely the frequency of watering (P1 = Watering once a day, P2 = Watering twice a day) and the use of various types of mulch (M0 = Without the use of mulch, M1 = straw mulch, and M2 = Silver black plastic mulch). The results showed that P2M2 treatment was the best treatment on plant height growth parameters (27.92 cm, 43.41 cm, 62.33 cm), number of leaves (60. 83 strands, 106.75 strands, 148.00 strands) age 14, 21, 28 HST, Flowering age (21.00 days) and fruit weight per sampel (2283.66 grams).